1+3(6b-3)=-134

Simple and best practice solution for 1+3(6b-3)=-134 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1+3(6b-3)=-134 equation:


Simplifying
1 + 3(6b + -3) = -134

Reorder the terms:
1 + 3(-3 + 6b) = -134
1 + (-3 * 3 + 6b * 3) = -134
1 + (-9 + 18b) = -134

Combine like terms: 1 + -9 = -8
-8 + 18b = -134

Solving
-8 + 18b = -134

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 18b = -134 + 8

Combine like terms: -8 + 8 = 0
0 + 18b = -134 + 8
18b = -134 + 8

Combine like terms: -134 + 8 = -126
18b = -126

Divide each side by '18'.
b = -7

Simplifying
b = -7

See similar equations:

| (3/5)x=6 | | 13=-1/2y | | y=0.5+1 | | 5/(x+4)-6x/(3x+12)+7/(2x+8) | | 1/2m=35 | | .6x=1.5 | | 15x-9=13x-9 | | 8x-4(-7.5)=2 | | 6x-4y= | | 2p+3p-p=9-15-6 | | 180=(x+5)(x+1)x | | 6(0.15+w)=10 | | Z-4.6=-2.2-3z | | 8q-42=-26 | | -54=6z-18 | | 3/2(2x-2)1/5= | | 2(3t-6)=10t-t-6 | | 0.3+2.6=4.4 | | (275)(373-x)(.444)=(100)(x-295)(4.184) | | 3y+10=82 | | -1/7y^7*5/8y^2 | | 5m+25=-65 | | 2x=6-y | | 3.7x-4=2.7x | | (6x-3)(-2x-14)= | | (-6x+3)(2x-14)= | | (-3x+9)(4x-2)= | | 6*9-9y=-54 | | c^2=2c+35 | | 9.7/5.9 | | y^2+100=20y | | (x+1)(x-1)(x-8)=0 |

Equations solver categories